Helical transition metal complexes as catalysts for asymmetric sulfoxidations and aldol addition reactions - Barman, Sanmitra (Kansas State University, 2010)
Stepped helical salen complexes with vanadium as the central metal were synthesized and characterized. The helicity in these complexes arise from the fused phenyl rings (phenanthryl and benz[a]anthryl) as sidearms, whereas the chirality arises from the chiral cyclohexyl diamine or binaphthyl diamine backbones. These complexes showed good yields and moderate enantioselectivity in asymmetric sulfoxidation reactions with methylphenyl sulfide as the substrate and H2O2 or cumene hydroperoxide as the oxidants. To further improve the closed nature of these complexes with a tetradentate salen ligand, we synthesized and characterized vanadium complexes with tridentate (S)-NOBIN backbone Schiff base ligands with phenanthryl and benz[a]anthryl as the sidearms. After initial catalytic study, we concluded that these catalysts are too open in nature to impose face selection during asymmetric induction. We also synthesized and characterized vanadium and titanium salan complexes. These complexes can adopt β-cis geometry, thereby making the complex “chiral at metal” and they are known for better catalysts in terms of asymmetric induction than their unreduced counterparts. However, these complexes showed better catalytic activity than their unreduced counterparts in sulfoxidation reactions with methylphenyl sulfide as the substrate and H2O2 or cumene hydroperoxide as the oxidants. We also put an effort to synthesize mixed salen complexes with vanadium as the central metal. These complexes have two different sidearms attached to one backbone unit. However, our method did not work well to produce pure mixed salen ligands. The catalysis results for mixed salen vanadium complexes are also comparable to the unreduced vanadyl salen complexes. Lastly, we synthesized and characterized new helical titanium Schiff base complexes with (S)-NOBIN backbone and phenanthryl and benz[a]anthryl sidearms. Single crystal studies showed that these complexes exist in the M helical conformation in the solid state. These complexes showed moderate activity in asymmetric aldol addition reactions between 2-methoxy propene and different aldehydes.
Keywords: Helical Metal Salen Complexes; Asymmetric Catalysis; Chemistry, Inorganic (0488)